Insect herbivory dampens Subarctic birch forest C sink response to warming - Silfver, Tarja; Heiskanen, Lauri; Aurela, Mika; Myller, Kristiina; Karhu, Kristiina; Meyer, Nele; Tuovinen, Juha-Pekka; Oksanen, Elina; Rousi, Matti; Mikola, Juha
2020